2006
DOI: 10.1111/j.1365-2915.2006.00643.x
|View full text |Cite
|
Sign up to set email alerts
|

The zoophilic fruitfly Phortica variegata: morphology, ecology and biological niche

Abstract: Flies belonging to the subfamily Steganinae (Drosophilidae) display unusual zoophilic feeding habits at the adult and/or larval stage. Phortica variegata (Fallén) feeds on tears or eye liquid around the eyes of humans and carnivores. When feeding it is a potential vector of Thelazia callipaeda (Railliet and Henry) eyeworms. Adult and larval stages of this fly may be easily confused with other species belonging to the same genus, and little is known on the biology and ecology of P. variegata. In April-November … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
102
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(110 citation statements)
references
References 14 publications
8
102
0
Order By: Relevance
“…The presence of a potential vector, the zoophilic fruitfly P. variegata, which is a known vector and intermediate host of T. callipaeda in southern Italy, has been reported in southern and central Ticino (http://www.taxodros.unizh.ch/, compiled by G. Bächli). This territory is also predicted to be a suitable habitat for P. variegata flies based on a predictive geoclimatic model (Otranto et al, 2006a). Additionally, a dog population of approximately 20'000 in the study area and an overall prevalence of 5.3% suggest that more than a thousand dogs could be infected and contribute to the expansion of thelaziosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a potential vector, the zoophilic fruitfly P. variegata, which is a known vector and intermediate host of T. callipaeda in southern Italy, has been reported in southern and central Ticino (http://www.taxodros.unizh.ch/, compiled by G. Bächli). This territory is also predicted to be a suitable habitat for P. variegata flies based on a predictive geoclimatic model (Otranto et al, 2006a). Additionally, a dog population of approximately 20'000 in the study area and an overall prevalence of 5.3% suggest that more than a thousand dogs could be infected and contribute to the expansion of thelaziosis.…”
Section: Resultsmentioning
confidence: 99%
“…An ecological niche model suggested that the climate of large areas of Europe could be suitable habitats for this vector (Otranto et al, 2006a) and thus are potentially endemic for T.…”
Section: Introductionmentioning
confidence: 99%
“…The misidentified D. suzukii and D. busckii larvae belonged to a Diptera species of the Drosophilidae family, genus Phortica according to sequencing results. This genus was reported in France according to previous survey (Otranto, Brianti, Cantacessi, Lia, & Máca, 2006), but not in the Rhone‐Alpes region (Withers & Allemand, 2012). …”
Section: Resultsmentioning
confidence: 68%
“…Infection is endemic in dogs. It occurs during the most intensive vector activity in the warm period of the year (19). T. callipaeda firststage larvae (L 1 ) can be found in the lachrymal secretions of dogs in summer (June-July), when infections of intermediate hosts occur.…”
Section: Resultsmentioning
confidence: 99%
“…Although humans are competent hosts, they usually act as accidental final hosts, in whom the third-stage larvae can grow into adults, but without epidemiologic effects on parasite transmission (7). All cases of thelaziosis in humans were reported during summer, in the period of the most intensive vector activity (19,21). The occurrence of thelaziosis and allergic (pollen-induced) conjunctivitis in humans in spring and summer may affect the validity of the etiological diagnosis of this disease.…”
Section: Tab 2 Intensity Of Infection and Location Of Thelazia Callmentioning
confidence: 99%